C3‐Symmetric Boron Lewis Acid with a Cage‐Shape for Chiral Molecular Recognition and Asymmetric Catalysis. Issue 6 (22nd December 2016) - Konishi, Akihito; Nakaoka, Koichi; Maruyama, Hikaru; Nakajima, Hideto; Eguchi, Tomohiro; Baba, Akio; Yasuda, Makoto
Abstract: Chiral Lewis acids play an important role in the precise construction of various types of chiral molecules. Here, a cage‐shaped borate2 was designed and synthesized as a chiral Lewis acid that possesses a unique C 3 ‐symmetric structure composed of three homochiral binaphthyl moieties. The highly symmetrical structure of2 with homochirality was clearly elucidated by X‐ray crystallographic analysis. The peculiar chiral environment of2 ⋅THF exhibited chiral recognition of some simple amines and a sulfoxide. Moreover, the application of2 ⋅THF to hetero‐Diels–Alder reactions as a chiral Lewis‐acid catalyst afforded the enantioselective products, which were obtained through an entropy‐controlled pathway according to the analysis of the relationship between optical yield and reaction temperature. In particular, the robust chiral reaction field of2 ⋅THF allowed the first example of an asymmetric hetero‐Diels–Alder reaction with a simple diene despite the requirement of high temperature. Abstract : Chiral cage‐shaped borate : A C 3 ‐symmetric cage‐shaped borate with homochiral binaphthyl cores is synthesized and characterized as a single diastereomer. This borate exhibits chiral recognition and behaves as a chiral Lewis‐acid catalyst with an unusual relationship between stereoselectivity and temperature. The robust and highly symmetric chiral environment provided by the binaphthyl cores characterizes the peculiar stereoselective reactivity.